Never back down. Revolt [videorecording (DVD)] - Arkins, Audrey; Popica, Olivia; Bisping, Michael, 1979-; Johnson, Brooke, 1962-; Faulkner, James, 1948-; Calchetti, Gianni; Al Rashid, Hannah (Sony Pictures Home Entertainment, 2021)
A woman is kidnapped and forced to compete in elite underground fights and has to battle her way out to freedom.